Vaname Shrimp (Litopenaus Vannamei) Hatchery Technique At CV. Manunggal 23, Serang District, Banten - Adi, Catur Pramono; Aripudin, Aripudin; Prabowo, Guntur; Eny Kristiany, Maria Goreti; Luthfiadi, Nabila Azzahra; Wirata, Wirata (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2023)
Improper shrimp hatchery can have an impact on the low level of fry quality so that fry production results also decrease. Therefore, quality vannamei shrimp hatcheries must be handled appropriately in accordance with standard operating procedures that have been implemented so that they are marketable. So it is necessary to study more deeply about the vannamei shrimp hatchery, especially the vannamei shrimp hatchery technique. The purpose of this study is to find out a number of things including: Operational Standards for Vanname Shrimp Hatchery; Gonad maturity performance; and Post-harvest activities of vanname shrimp hatchery. The shrimp hatchery technique uses analysis by calculating the Fertilization Rate (HR) and Hatching Rate (HR). Based on the results of the study it was found that: 1). The technical aspects of the CV Manunggal 23 shrimp hatchery in general are in accordance with the standard procedures referred to. 2). The broodstock productivity performance at CV Manunggal 23 has a good rate with an average HR of 75.83% and FR of 62% within 3 weeks. 3). Water Quality in CV. Manunggal 23 achieved optimal numbers with an average temperature of 27-28°C, pH 8, DO 5.5-5.6 mg/L, and Salinity 32-33 ppt within 3 weeks.